A multifunctional polyurethane sponge based on functionalized graphene oxide and carbon nanotubes for highly sensitive and super durable fire alarming. (November 2021) - Chen, Zhu; Chen, Wenhua; Liu, Pengju; Liu, Yuan; Liu, Zhuoxin
Graphical abstract: Highlights: A highly sensitive and super durable fire alarming sensor was prepared. Sponge showed a short response time of 1 s and long alarming period of 2640 s. Sponge acted as a piezoresistive sensor to detect wide range of compressive strain. Abstract: The lightweight materials with good flame retardancy and early fire alarming function can play an effective role in reducing the potential loss caused by fire disasters, which will be highly demanded in the interior decoration of automobile and house. Herein, a multifunctional polyurethane sponge (PUS) was prepared by depositing the flame retardant-modified graphene oxide (FGO) and chitosan-functionalized carbon nanotubes (CNTs) through the layer-by-layer (LBL) assembly. A compact protective barrier formed by combining the chemical char from the catalytic carbonization of PUS and the physical carbon of FGO/CNTs, offering ultra-high structural stability during flame treatment process. The coated sponge showed a short alarming time of ~1 s in fire and a early alarming time of ~2 s at 500 °C, along with a super-long alarming period of 2640 s. Besides, FGO/CNTs@PUS could also acted as a stable piezoresistive sensor to detect the wide range of compressive strain and finger motions.